Collusive behaviour in the automobile sector in Spain. Quantifying consumer damages - Sánchez-Sánchez, Mercedes Nuria; Fernández-Puente, Adolfo Cosme (Revista de Estudios Andaluces, 2024)
On July 23, 2015, the Spanish National Markets and Competition Commission (CNMC) passed judgement (S/0482/13) against 20 automotive sector companies for alleged restrictive competition practices between March 2004 and August 2013. The exchange of information among the different companies would have had repercussions on the fixing of vehicle sale prices, homogenization of conditions and future commercial plans for the automobile sale and post-sale services in Spain. This paper estimates the loss suffered by consumers as a result of these collusive practices using the Before and After method. We have reconstructed the prices that would have prevailed in the absence of the collusive practice. The analysis reveals an increase of 10.16 percent. The observation of the prices and the production of automobiles during the period exhibits an anomalous behaviour with respect to GDP evolution and prices in the economy as a whole.